Structural Errors in Arabic Sentence Formation among Kurdish Preparatory Stage School Students - Erbil Schools as a Model: Educational Challenges and an Analytical Perspective in Light of Artificial Intelligence - Ismail, D. Dilshad Jalil Ismail (Sulaimani Journal for Humanities, 2025)
Arabic language teachers in linguistically diverse settings, particularly in the Kurdistan Region, face numerous challenges and obstacles in teaching non-native Arabic-speaking middle school students how to construct and form sentences correctly. Structural errors are among the most common problems students encounter in speaking and writing, negatively impacting their performance and language acquisition and skills. This research aims to analyze common syntactic errors among Kurdish students, highlight the difficulties and challenges teachers face in teaching linguistic structures, and explore ways to apply artificial intelligence to diagnose and correct language problems. The research adopts a descriptive-analytical approach, combining a theoretical analysis of the concept of syntactic errors and their educational aspects with an applied analysis of a sample of Kurdish middle school students' writing. The research also provides examples of artificial intelligence tools that can be integrated into the Arabic language teaching and learning process, such as automated language correctors and smart teaching platforms. The most notable findings include: 1. Many syntactic errors are attributed to the influence of the mother tongue (Kurdish). 2. Weak teaching and training in practical Arabic sentence formation. 3. The results also demonstrated the effectiveness of using artificial intelligence tools in improving Kurdish students' performance and increasing their awareness of the errors they make when forming Arabic sentences. 4. The research recommendations and suggestions include updating teaching methods and approaches, developing interactive educational programs and activities based on artificial intelligence, and training teachers to integrate these technologies into a multilingual environment.
Keywords: structural errors; Kurdish students; Arabic language teaching; educational challenges; and artificial intelligence